Does high cardiorespiratory fitness confer some protection against pro-inflammatory responses after infection by SARS-CoV-2? - Zbinden-Foncea, H.; Francaux, M.; Deldicque, L.; Hawley, J. A. (Obesity, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) originated in China in late 2019 and has since spread rapidly to every continent in the world. This pandemic continues to cause widespread personal suffering, along with severe pressure on medical and health care providers. The symtoms of SARS-CoV-2 and the subsequent prognosis is worsened in individuals who have pre-exisiting comorbidities prior to infection by the virus. Individuals with obesity/overweight, insulin resistance and diabetes typically have chronic low-grade inflammation characterized by increased levels of several pro-inflammatory cytokines and the inflammasome: this state predisposes to greater risk for infection along with more adverse outcomes. Here we consider whether a high level of cardiorespiratory fitness induced by prior exercise training may confer some innate immune-protection against Covid-19 by attenuating the "cytokine storm syndrome" often experienced by "at risk" individuals.